1978
DOI: 10.1083/jcb.79.1.184
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of horseradish peroxidase (HRP)-anti-HRP immune complexes in mouse spleen with special reference to follicular dendritic cells.

Abstract: The distribution of immune complexes has been studied in mouse spleen stimulated to contain many germinal centers (GC's). Horseradish peroxidase (HRP)-anti-HRP complexes were used as an appropriately precise and sensitive model. We were primarily interested in the relative abilities of three cell types to interact with complexes: lymphocytes, macrophages, and follicular dendritic cells (FDC's). The latter are distinctive, nonendocytic, stellate cells located primarily at the transition of mantle and GC zones o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

1980
1980
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 27 publications
1
38
0
1
Order By: Relevance
“…An example of the latter is the retention of antigen-antibody complexes in the germinal center region of lymphoid organs. Chen et al (16), using horseradish peroxidase (HRP) as a marker, have shown that small amounts of HRP-anti-HRP immune complexes formed in antigen excess escape phagocytosis and instead associate with the cell surface of nonphagocytic follicular dendritic cells~ In this regard it is important to note that we have found that the mQst effective antigen presentation is performed by cells that are weakly phagocytic (Langerhans cells) or nonphagocytic (splenic dendritic cells, vide lhfra). (c) A third way of eliciting short-lived CS is by injecting the antigen-conjugated cells, that are predominantly macrophages, in such a way that primary immunization occurs in peripheral lymph nodes (3).…”
Section: Discussionmentioning
confidence: 99%
“…An example of the latter is the retention of antigen-antibody complexes in the germinal center region of lymphoid organs. Chen et al (16), using horseradish peroxidase (HRP) as a marker, have shown that small amounts of HRP-anti-HRP immune complexes formed in antigen excess escape phagocytosis and instead associate with the cell surface of nonphagocytic follicular dendritic cells~ In this regard it is important to note that we have found that the mQst effective antigen presentation is performed by cells that are weakly phagocytic (Langerhans cells) or nonphagocytic (splenic dendritic cells, vide lhfra). (c) A third way of eliciting short-lived CS is by injecting the antigen-conjugated cells, that are predominantly macrophages, in such a way that primary immunization occurs in peripheral lymph nodes (3).…”
Section: Discussionmentioning
confidence: 99%
“…Spleens were removed next day, and the HRP Ag was detected by DAB histochemistry on cryosections. At this time point, FDCs in the GC region of the spleen are the only cell types with extracellular enzyme (17). ICs were readily trapped on FDCs in control mice (Fig.…”
Section: Lack Of Fdc Network and Ic Trapping In Relb-deficient Micementioning
confidence: 97%
“…For IC trapping, mice were immunized with SRBCs, and 6 days later injected i.v. with 200 g preformed peroxidase antiperoxidase ICs (Dako Diagnostika, Hamburg, Germany) (17). Spleens were removed 24 h later, embedded in Polyfreeze (Polysciences, Warrington, PA), and stored at Ϫ80°C.…”
Section: Immunizations and Ic Trappingmentioning
confidence: 99%
“…For immune stimulation, we treated mice with either preformed immune complexes (ICs) of HRP and mouse-monoclonal anti-HRP IgG, or vesicular stomatitis virus (VSV), a member of the Rhabdoviridae family. Treatment with preformed ICs has been reported to lead to IC trapping on the surface of FDCs and presentation to germinal center B cells (14). An infection with VSV, in contrast, is defeated primarily by a neutralizing IgM response, but also elicits a germinal center reaction that is characterized by longtime persistence of VSV Ag on FDCs and the maintenance of a memory IgG titer (15).…”
mentioning
confidence: 99%